Saving fish from drowning - Tan, Amy (Reader's circle, 2006)
A pious man explained to his followers: "It is evil to take lives and noble to save them. Each day I pledge to save a hundred lives. I drop my net in the lake and scoop out a hundred fishes. I place the fishes on the bank, where they flop and twirl. 'Don't be scared, ' I tell those fishes. 'I am saving you from drowning.' Soon enough, the fishes grow calm and lie still. Yet, sad to say, I am always too late. The fishes expire. And because it is evil to waste anything, I take those dead fishes to market and I sell them for a good price. With the money I receive, I buy more nets so I can save more fishes."--Anonymous ; twelve American tourists join an art expedition that begins in the Himalayan foothills of China--dubbed the true Shangri-La--and heads south into the jungles of Burma. But after the mysterious death of their tour leader, the carefully laid plans fall apart, and disharmony breaks out among the pleasure-seekers as they come to discover that the Burma Road is paved with less-than-honorable intentions, questionable food, and tribal curses. And then, on Christmas morning, eleven of the travelers boat across a misty lake for a sunrise cruise--and disappear. Drawing from the current political reality in Burma and woven with pure confabulation, Amy Tan's picaresque novel poses the question: How can we discern what is real and what is fiction, in everything we see? How do we know what to believe?